THE VIEWS OF THE BOOK AL-MAJMU' SYARH AL-MUHADZDZAB, IMAM AL-NAWAWI ON THE LAW OF BANK INTEREST - M. Doni; Arsal Arsal (Adisam Publisher, 2026)
The issue of bank interest is still an important debate in the study of Islamic economics, especially related to its legal status which is associated with the prohibition of usury in the Qur'an and Sunnah. This study aims to analyze the law of bank interest based on the perspective of classical fiqh by focusing on the views of Imam al-Nawawi in the book Al-Majmu' Syarḥ al-Muhadzdzab. This study uses a qualitative method with a normative approach through literature studies. The main source of data is the book Al-Majmu' by Imam al-Nawawi, which is supported by classical and contemporary fiqh literature, scientific journals, and fatwas of relevant Islamic institutions. The data was analyzed using a descriptive-analytical method by examining additional concepts (ziyādah) in loan contracts (al-qardh) and the classification of usury, especially riba nasi'ah, then relating them to bank interest practices in the modern banking system. The results of the study show that Imam al-Nawawi expressly stated that any addition required in the debt-receivables contract is forbidden riba and causes the contract to become a façade. In addition, additions that are based solely on the delay of time are included in the category of riba nasi'ah whose haram has been agreed upon by the scholars. Based on this framework, bank interest which is certain, determined from the beginning of the contract, and based on time substantially meets the criteria of riba according to the view of Imam al-Nawawi. Thus, from the perspective of the Shafi'i school, bank interest is included in riba and the law is haram, so that the development of the Islamic financial system is an urgent need to realize justice and economic benefits.